ANALISIS KETUNTASAN PEMBELAJARAN ONLINE PADA MATAKULIAH BAHASA INGGRIS - Edi Faizal; Andhina Ika Sunardi (LPPM STMIK El Rahma Yogyakarta, 2021)
The pandemic due to the corona virus at the end of 2019 (covid-19) has caused changes in the order of life, including education. Social and physical distancing in tackling the spread of Covid-19 affect the learning model. Starting from early childhood education to the university level applying an online learning model. This study analyzes the completeness of the online model of learning English. The analysis was carried out by using profile matching method on 430 student data from three universities in Yogyakarta. Completeness of learning is divided into 5 levels based on 4 components. The results showed that the level of completeness of online learning in all areas of higher education was 89.1%. The analysis of the results shows that the level of learning completeness of IT students is better than non-IT students, respectively 90.5% (IT) and 88.6% (Non-IT).